Pulmonary Histopathology in Cats and Dogs with Fatal Tick Paralysis. (September 2022) - Wang, Yachen; Watters, Natalie; Jones, Emily; Padula, Andrew; Leister, Ellie; Haworth, Mark; Henning, Joerg; Allavena, Rachel
Summary: The objective of this study was to evaluate critically the nature and prevalence of histological pulmonary lesions in dogs and cats that had died or were euthanized because of tick paralysis. A retrospective and prospective case study of 11 cats and 23 dogs was carried out. Retrospective cases were gathered from the Veterinary Laboratory Services database at The University of Queensland (UQ). Prospective cases were provided by Veterinary Specialist Services and UQ VETs Small Animal Hospital. Lung and other tissue samples were collected for histopathological analysis. All tick intoxicated animals demonstrated evidence of pulmonary parenchymal changes: alveolar oedema, interstitial and alveolar congestion and alveolar fibrin exudation. Eleven of 23 (48%) dogs exhibited mild to severe bronchopneumonia. A lower rate (18%) of bronchopneumonia was found in cats, with one case of aspiration pneumonia. A novel pulmonary histological grading scheme was developed to evaluate the correlation between clinical presentation and histopathological changes. Novel extrapulmonary lesions in cats included hepatic necrosis and acute renal tubular necrosis attributed to hypoxia. We concluded that both dogs and cats with high clinical grade tick paralysis are extremely likely to have pulmonary pathology. High-protein oedema and fibrin exudation are predicted to be present in most cases of canine and feline tick paralysis.